(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In the article, the application of the demonstration method of experimental training (TMKM) in the educational process creates a foundation for new education, pedagogical solutions to ensure the consistency of education and the inclusion of "Fuel and lubricants" in educational and scientific programs are highlighted.